(untitled) - Roach, Peter (Oxford, 2001)
This book leads the reader through the main areas of phonetics, including how speech sounds are made and how phoneticians classify them. Topics include the International Phonetic Alphabet, intonation, and accent variation.
Keywords: Phonetics